Niger : Ex Post Assessment of Longer-Term Program Engagement. (IMF Staff Country Reports; Country Report ;, 2011)
IMF engagement with Niger since 2005 has remained constructive. IMF-supported programs have contributed to the authorities' goals of macroeconomic stability, growth, and human development progress. Development of Niger's uranium and petroleum resources provides an important opportunity to raise the living standards of Niger's citizens. Institutional reforms aimed at enhancing the efficient use of resource revenues and transparency of public finances will remain critical to maximize benefits and avoid distortions associated with the resource curse.